Waldflurbereinigung in Bayern. Eine akteurtheoretische Analyse. - Gaggermeier, Anika (My University, 2014)
Die Arbeit beschäftigt sich mit der Waldflurbereinigung als ein Lösungsinstrument gegen die Fragmentierung kleinflächiger Privatwaldstrukturen in Bayern. In drei Fallstudien werden mit Hilfe von Methoden der qualitativen Sozialforschung und des Prinzips des "Methodologischen Individualismus" die Konstituierungs- und Entwicklungsprozesse sowie die Bewertung der Waldflurbereinigung aus Sicht der beteiligten Akteure analysiert. Bei den Befragten zeichnet sich eine hohe Zufriedenheit mit dem Verfahren und dem Zustand ihres Waldeigentums nach der Waldflurbereinigung ab.

The present study deals with forest land consolidation as a solution to the fragmentation of small-scale private forests in Bavaria. In three case studies, the processes of initiation and development as well as the evaluation of forest land consolidation were analyzed from the perspective of the involved stakeholders. For this purpose, the principle of "Methodological Individualism" as well as qualitative methods of social research were applied. The interviewees were found to be highly satisfied with the process and the state of their forest property after the forest land consolidation.
Forest Land Consolidation in Bavaria. A stakeholder-theoretical analysis.
Keywords: Forstwirtschaft; Forstpolitik; Flurbereinigung; Privatwald; Waldbesitz; Kooperation; Befragung; Empirische Untersuchung; Akteur; Strukturverbesserung; Waldpflege; Nachhaltigkeit